2019
DOI: 10.1007/s10994-019-05808-z
|View full text |Cite
|
Sign up to set email alerts
|

Grouped Gaussian processes for solar power prediction

Abstract: We consider multi-task regression models where the observations are assumed to be a linear combination of several latent node functions and weight functions, which are both drawn from Gaussian process priors. Driven by the problem of developing scalable methods for forecasting distributed solar and other renewable power generation, we propose coupled priors over groups of (node or weight) processes to exploit spatial dependence between functions. We estimate forecast models for solar power at multiple distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The present study was motivated by previous research by other authors such as Zhandire [2], Mpfumali et al [3], Govender et al [4] and Mutavhatsindi et al [5]) Marizt [14], Bonilla [16], Dahl and Bonilla [17], among others, and the proposed method was developed. A new approach to solar power forecasting was done and the Gaussian process regression approach was used based on core vector regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was motivated by previous research by other authors such as Zhandire [2], Mpfumali et al [3], Govender et al [4] and Mutavhatsindi et al [5]) Marizt [14], Bonilla [16], Dahl and Bonilla [17], among others, and the proposed method was developed. A new approach to solar power forecasting was done and the Gaussian process regression approach was used based on core vector regression.…”
Section: Discussionmentioning
confidence: 99%
“…They applied several kernels and found that the quasi-periodic kernels outperformed most of them. Research on forecasting of solar power using grouped Gaussian processes was done by Dahl and Bonilla [17]. They applied to multitask GP models with observations being linear with several latent node functions and also based on weight functions on priors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is not just a question of accounting. Reliable open data about renewable power sources will enable significant additional CO2e (carbon dioxide equivalent) savings-through various means including short-term output forecasting 5,6 [Section 1.1.1], demand forecasting 6 [Section 1.1.1], fleet management, and capacity expansion-and thus contribute significantly to reducing the impact of the climate crisis at national and international scale 7 . "Open data" here refers to data published and licensed permissively in such a way that it can be reused by third parties for a very wide variety of purposes, without need for any direct licensing arrangements; at the national scale, open data has significant economic benefits [8][9][10][11] .…”
Section: Background and Summarymentioning
confidence: 99%
“…Yadav et al [29] provide an overview of neural networks as prediction models, while Sharma et al [30] study machine learning based on weather forecasts, including the sky coverage, using support vector machines. Alternatively, Dahl and Bonilla [31] use Gaussian Processes as a forecasting model, which can also quantify the confidence level in the prediction estimate. Benali et al [32] use separate models for the different components of radiation.…”
Section: Related Workmentioning
confidence: 99%